Review on Shariah Supervisory Board Studies using Bibliometrix - Puspita, Amelia Tri; Ali, Mohammad Mahbubi (Maqasid al-Shariah Review, 2023)
The rapid development of the Indonesian economy is influenced by the emergence of both sharia and non-sharia financial institutions. In Islamic banking, so that all parties' interests can be met properly, the management and supervision structure will involve four parties, namely: shareholders (board of commissioners), bank management, Sharia Supervisory Board (DPS) and/or National Sharia Council (DSN), and depositors. In an effort to purify the services of Islamic financial institutions to be truly in line with the provisions of Islamic sharia, the existence of a Sharia Supervisory Board (DPS) is absolutely necessary. DPS is a key institution that ensures that the operational activities of Islamic financial institutions are in accordance with sharia principles. This study aims to determine the development map and trend of Shariah Supervisory Board published by reputable journals in the field of Economics and Islamic finance. The data analyzed were more than 114 publications of research publications indexed by Scopus. The export data was then processed and analyzed using the R Biblioshiny application program to determine the bibliometric map of the development of the Shariah Supervisory Board.